TYPICAL ENDOPHORIC MARKERS USED BY STUDENTS OF ELESP OVER CHAPTER FOUR - Belinda, Mita (Journal of English Teaching and Linguistics Studies (JET Li), 2024)
The paper entitled “Typical Endophoric Markers used by Students of ELESP over Chapter Four” is aimed to find out the typical of endophoric markers which are used in quatitative research papers by ELESP students. In conducting this research, the writer applied descriptive method to describe the result of the research. The writer conducted via online (WhatApps and Google Form). The participants were 10 who have finished their chapter four. The writer used random sampling in this research to conduct and selected the participants. The research data were obtained from three instruments: documentation, questionnaire and interview. The documents were taken from quantitative research papers. The questionnaire distributed and the interview were done to the students who used highly endophoric markers for completing the data. The writer found there were several typical endophoric markers that were used over chapter four of ELESP students research papers, namely in Table 4.2, according to Table 4.1 below, at Figure 4.3, the polygon graph above, on Table 4.1 and based on the calculation above. The writer also found out that endophoric markers facilitated the students to present the data through table, diagram, polygon graph, histogram and figure by referring them in the explanation. Endophoric markers facilitated to connect between the data and explanation as a whole part. So that, the readers could comprehend them clearly. The students got typical which were used from other research papers and journal articles.